Science between Bioreactors and Space Research—Response to Comments by Joseph J. Bevelacqua et al. on “Dexamethasone Inhibits Spheroid Formation of Thyroid Cancer Cells Exposed to Simulated Microgravity” - Marcus Krüger; Sascha Kopp; Markus Wehland; Thomas J. Corydon; Daniela Grimm (Cells, 2020)
We would like to thank Bevelacqua et al [...]